Cadmium activation of wild-type and constitutively active estrogen receptor alpha - Psaltis, John B.; Wang, Qiaochu; Yan, Gai; Gahtani, Reem; Huang, Nanxi; Haddad, Bassem R.; Martin, Mary Beth (Frontiers in Endocrinology, 2024)
The estrogen receptor alpha (ERα) plays a central role in the etiology, progression, and treatment of breast cancers. Constitutively activating somatic mutations Y537S and D538G, in the ligand binding domain (LBD) of ESR1, are associated with acquired resistance to endocrine therapies. We have previously shown that the metalloestrogen calcium activates ERα through an interaction with the LBD of the receptor. This study shows that cadmium activates ERα through a mechanism similar to calcium and contributes to, and further increases, the constitutive activity of the ERα mutants Y537S and D538G. Mutational analysis identified C381, N532A, H516A/N519A/E523A, and E542/D545A on the solvent accessible surface of the LBD as possible calcium/metal interaction sites. In contrast to estradiol, which did not increase the activity of the Y537S and D538G mutants, cadmium increased the activity of the constitutive mutants. Mutation of the calcium/metal interaction sites in Y537S and D538G mutants resulted in a significant decrease in constitutive activity and cadmium induced activity. Mutation of calcium/metal interaction sites in wtERα diminished binding of the receptor to the enhancer of estrogen responsive genes and the binding of nuclear receptor coactivator 1 and RNA polymerase II. In contrast to wtERα, mutation of the calcium/metal interaction sites in the Y537S and D538G mutants did not diminish binding to DNA but prevented a stable interaction with the coactivator and polymerase. Growth assays further revealed that calcium channel blockers and chelators significantly decreased the growth of MCF7 cells expressing these constitutively active mutants.Taken together, the results suggest that exposure to cadmium plays a role in the etiology, progression, and response to treatment of breast cancer due, in part, to its ability to activate ERα.